1997
DOI: 10.1093/hmg/6.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 3p14 Homozygous Deletions and Sequence Analysis of FRA3B

Abstract: Loss of heterozygosity (LOH) involving 3p occurs in many carcinomas but is complicated by the identification of four distinct homozygous deletion regions. One putative target, 3p14.2, contains the common fragile site, FRA3B, a hereditary renal carcinoma-associated 3;8 translocation and the candidate tumor suppressor gene, FHIT. Using a approximately 300 kb comsid/lambda contig, we identified homozygous deletions in cervix, breast, lung and colorectal carcinoma cell lines. The smallest deletion (CC19) was shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
122
1

Year Published

1997
1997
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(127 citation statements)
references
References 40 publications
4
122
1
Order By: Relevance
“…All FHIT-speci®c variants observed in a given specimen by nested PCR were also found using the appropriate primer pair. These alternatively spliced transcripts were clearly no more prominent in the tumors than in the normal prostate specimens in keeping with results from Boldog et al (1997). The present result con®rms that FHIT variants are present at a far lower level (51%) than the full-length transcript in both normal and neoplastic prostate tissue.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…All FHIT-speci®c variants observed in a given specimen by nested PCR were also found using the appropriate primer pair. These alternatively spliced transcripts were clearly no more prominent in the tumors than in the normal prostate specimens in keeping with results from Boldog et al (1997). The present result con®rms that FHIT variants are present at a far lower level (51%) than the full-length transcript in both normal and neoplastic prostate tissue.…”
Section: Discussionsupporting
confidence: 89%
“…As the FHIT open reading frame is contained in exons 5 ± 9 (Figure 1a), it is unlikely that most of these alternatively spliced transcripts encode functional proteins. The absence of exon 8, which contains the histidine triad domain, is also one of the most frequent variation observed in breast cancer , squamous cell carcinomas of the head and neck (Virgilio et al, 1996), renal cell carcinomas (Luan et al, 1997), and also in normal fetal brain cDNA (Boldog et al, 1997), whereas loss of exon 3, that¯anks the t(3;8) translocation, has been observed in the prostate cancer-derived cell line LNCaP .…”
Section: Discussionmentioning
confidence: 99%
“…First, although in agreement with previous reports of other human malignancies Ohta et al, 1996;Sozzi et al, 1996a,b), aberrant transcripts of the FHIT gene were frequently detected in the tumorous liver tissues, they also existed in the nontumorous liver tissues. Recently, Boldog et al reported the presence of the aberrant FHIT transcripts in the normal fetal brain cDNA and concluded that the alternative splicing definitely occurs in normal human tissues (Boldog et al, 1997). This is consistent with our findings and may explain the currently and most previously reported abnormal FHIT transcripts.…”
Section: Microsatellite Polymorphism Analysissupporting
confidence: 92%
“…The structural alterations of FRA3B might interfere with the normal splicing and thus result in the generation of numerous aberrant transcripts. Indeed, homozygous deletions in the FHIT gene mostly involve intronic sequences within the FHIT gene locus (Boldog et al, 1997), suggesting that partial deletions of the FHIT gene might affect transcription fidelity. Previous reports indicated that breakage and rearrangements of DNA within the FHIT gene resulted in occurrence of aberrant transcripts and subsequently reduced FHIT protein expression Baffa et al, 1998).…”
Section: Discussionmentioning
confidence: 99%